(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the use of gamification in English language teaching has transformed traditional learning by integrating interactive and game-based elements to boost student engagement, motivation, and academic performance. This research explores how various gamification features—such as rewards, leaderboards, challenges, and storytelling—contribute to creating a more engaging and immersive learning experience. By contrasting conventional teaching methods with gamified approaches, the study assesses the effectiveness of game-based strategies in enhancing student participation, knowledge retention, and language proficiency. The results emphasize the advantages of gamification in promoting active learning and long-term interest, while also considering challenges like excessive reliance on rewards and difficulties in incorporating technology into the curriculum. The study offers practical insights for educators on successfully implementing gamification to improve English language instruction.